KRITERIA RUMAH ISLAMI - -, Andi Isdyanto (Teknosains, 2014)
The house is one of the important things that are involved in the formation of a family. Home is where the back of traveling, as well as the most fundamental place in mentarbiyah self and family. Hence the formation of the basic nature of a human being. For that how to meet the home in accordance with the Islamic criteria and create a healthy home environment as well as Islamic is we need to know in order to house the coveted always in a pleasant atmosphere and Islamic for mental development of all family members. For that in choosing or building a home should meet the criteria in accordance with the Islamic criteria . What are the criteria for Islamic home ie : Choosing the right location means adjacent to the place of worship, Choosing the right neighbor, does not boast in building houses, making houses spacious and clean and nice houses and beautiful. So with the fulfillment of an Islamic house criteria we can make it as ameans of rest after working; making it a means of protection when there is danger, rain, heat and cold; making it a compassionate family; making it a means of gathering of relatives, neighbors, and friends; and also makes for a solemn worship of the almighty.Keywords: Criteria, House, Islamic design.